Diseño de material ilustrado como apoyo en la asignatura de ciencias naturales en la “Unidad Educativa General Eloy Alfaro Delgado” en la ciudad de Ambato. - Llamuca Montenegro, Luis Miguel (2024)
This project focuses on the design of illustrated editorial material to support the teaching of natural sciences at the Gral. Eloy Alfaro Delgado Educational Unit in Ambato. Education in the country faces challenges especially in the subject of natural sciences since its context is difficult for students to understand, which justifies the need for a proposal that improves the quality of educational materials. This work seeks to develop a graphic system that interprets literary articles through various illustration techniques, thus facilitating the learning and understanding of complex scientific concepts. The methodology used includes a preliminary diagnosis that reveals problems in the current design and the subject matter to be treated in this research, as well as interviews with teachers to obtain qualitative information about the most appropriate illustration techniques. The results indicate that the implementation of an attractive and functional graphic design can significantly improve the communication of key ideas and foster more effective learning in students. In conclusion, the creation of editorial material is proposed that not only addresses natural science content, but also uses innovative illustration techniques to capture the attention of students. This approach seeks to inspire curiosity and critical thinking, contributing to the comprehensive development of students and their preparation to face the challenges of today's world in their context. The implementation of this proposal is considered essential to improve educational quality in the Educational Unit.